Pembelajaran Berbasis Masalah K13 dan Kurikulum Merdeka untuk Meningkatkan Kemampuan Belajar Siswa - Aci Rahmawati; Neng Solihat (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Problem-Based Learning (PBL) is a student-centered teaching approach, where the learning process begins with a real-life problem relevant to everyday life. PBL encourages students to actively seek information, analyze data, and formulate solutions through group work and discussion. This approach not only develops critical thinking, problem-solving, and communication skills but also increases students' independence and responsibility for their own learning process. This article aims to examine how PBL is implemented in two main curricula in Indonesia: the 2013 Curriculum (K13) and the Independent Curriculum. In the 2013 Curriculum, PBL is integrated through a scientific approach and project-based activities, where students are invited to explore concepts and theories through investigative activities. Meanwhile, the Independent Curriculum provides more space for teachers and students to design contextual and personalized learning activities, making the implementation of PBL more flexible and adaptive to local needs and student characteristics. The literature review results indicate that both curricula effectively utilize PBL principles to enhance students' cognitive and metacognitive skills. The Independent Curriculum, in particular, places greater emphasis on independent learning, self-reflection, and the development of student interests through differentiated learning. Thus, the application of PBL within the context of the Independent Curriculum has proven to be more adaptive to the dynamics of 21st-century learning. In conclusion, the use of Problem-Based Learning in both curricula has significant potential to enhance students' learning abilities, as long as the approach is tailored to school conditions, student characteristics, and is supported by competent teachers and training in implementing this method effectively.